44 HUBUNGAN OBESITAS DENGAN RISIKO OBSTRUCTIVE SLEEP APNEA (OSA) PADA REMAJA - Rahman, Usep Basuki; -, Handoyo; Rahadi, Pujo (LPPM STIKES MUHAMMADIYAH GOMBONG, 2012)
The positive effect of the development process is to increase qualityand wealth live index. That situation has an impact of obesity frequencyby year. Meanwhile, obesity cases during teenagers could continue totheir live. That situation has influence of development chronicallydiseases and some health problems. One of disease that commonlydevelops for people who have obesity is obstructive sleep apnea (OSA).OSA become chronically situation if obesity is not detected in the earlydeveloped.The aim of this study is to analyze correlation of obesity with riskof obstructive sleep apnea in teenagers. This is a non experimentalresearch with analytic survey design by Cross sectional method thatlocated in SMA Negeri 1 Purwokerto. Obesity frequency was determinedby Body Height (BH) and Body Weight (BW) of student in SMA Negeri 1Purwokerto, sample collected that were 100 students, who randomlyselected. Obesity criteria was determined by IMT score more than orsame as 25 kg/m2. BH was measured by stature meter and BW wasmeasured by body scale with gradation of 0,1 kg, Risk of obstructivesleep apnea (OSA) by using Berlin questioner. Data analysis were usingChi-square test.Obesity frequency of SMA Negeri 1 Purwokerto student was 46%.meanwhile, frequency of obstructive sleep apnea (OSA) risk was 43%.Research result showed that there was correlation of obesity with risk ofobstructive sleep apnea (OSA) (p=0,000).Keywords: Obesity, Obstructive sleep apnea (OSA), Teenagers.